Correction: Efficient direct lignin fuel cells enabled by hierarchical nickel–iron phosphide nanosheets as an anode catalyst. Issue 9 (13th April 2023) - Liu, Fei; Lusi, A.; Radhakrishnan, Harish; Liu, Hengzhou; Li, Wenzhen; Qin, Hantang; Jiang, Shan; Bai, Xianglan; Hu, Shan
Abstract : Correction for 'Efficient direct lignin fuel cells enabled by hierarchical nickel–iron phosphide nanosheets as an anode catalyst' by Fei Liu et al., Sustainable Energy Fuels, 2022, 6, 4866–4872, ; https://doi.org/10.1039/D2SE00930G .